The Fekete-Szegö theorem for a certain class of analytic functions - Ma`Moun Harayzeh Al-Abbadi,; Maslina Darus, (Universiti Kebangsaan Malaysia, 2011)
In this paper, we discuss a well known class studied by many authors including Ramesha et al. and Janteng, few to mention. Next, we extend the class to a wider class of functions f denoted by , which are normalized and univalent, in the open unit disk D={z:|z|<1} satisfying the condition: where g ∈ S* (b),g(z) ≠ 0 is a normalized starlike function of order b, for 0 ≤ b < 1. For f ∈ we shall obtain sharp upper bounds for the Fekete-Szegö functional |a3 – μ | when μ is real.